Two-component polyurethane adhesive composition
The thermally conductive two-part polyurethane adhesive composition addresses the challenge of achieving high bond strength and elongation by using a specific formulation with poly(tetramethylene oxide) glycol, resulting in improved thermal conductivity and cohesive failure for electric vehicle battery applications.
Patent Information
- Application Number
- JP2024542085
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-12
- Filing Date
- 2023-01-06
- Publication Date
- 2025-01-24
AI Technical Summary
Existing thermally conductive two-part polyurethane adhesives struggle to simultaneously achieve high bond strength, excellent elongation, and thermal conductivity, particularly in applications like electric vehicle battery packs.
A thermally conductive two-part polyurethane adhesive composition comprising a polyisocyanate component with 40-85% thermally conductive filler and a polyol component containing poly(tetramethylene oxide) glycol, with a specific isocyanate-to-hydroxyl equivalent ratio of 0.8 to 2.0, along with optional silane adhesion promoters, is used to enhance bonding properties.
The adhesive achieves thermal conductivity exceeding 1.1 W/mK, lap shear strength of over 4 MPa with 50% elongation, and cohesive failure mode, suitable for bonding in electric vehicle battery assemblies.
Smart Images

Figure 2025502290000001 
Figure 2025502290000002 
Figure 2025502290000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of two-part polyurethane adhesive compositions. [Background technology]
[0002] Two-part polyurethane adhesives are commonly used to bond a variety of substrates such as glass, metal or coated metal, and plastics.
[0003] Thermally conductive two-part polyurethane adhesives are increasingly being used in applications such as bonding components in electric vehicle battery packs. Typically, two-part polyurethane adhesives provide good bond strength but lack sufficient elongation and toughness.
[0004] Two-part thermally conductive polyurethane adhesives are generally prepared by combining an isocyanate component and a polyol component. The polyol component comprises a polyether polyol, such as a polypropylene oxide polyol, or a blend of polyether polyols, such as polypropylene oxide polyols, having different molecular weights. Both the isocyanate component and the polyol component contain high levels of thermally conductive fillers, which affect the physical properties, especially the elongation. A typical two-part thermally conductive polyurethane adhesive cannot simultaneously obtain high bond strength and excellent elongation. Summary of the Invention [Problem to be solved by the invention]
[0005] There remains a need for thermally conductive two-part polyurethane adhesives that have excellent thermal conductivity, high bond strength and good elongation. [Means for solving the problem]
[0006] In a first aspect, the present invention provides a thermally conductive two-part polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B at least one of the polyether polyols in component A and component B is poly(tetramethylene oxide) glycol, and the equivalent ratio of the isocyanate derived from component A to the hydroxyl derived from component B is 0.8 to 2.0.
[0007] In a second aspect, the present invention provides a method for bonding two or more substrates, comprising the steps of: (1) providing a thermally conductive two-component polyurethane adhesive composition, the thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B at least one of the polyether polyols in component A and component B is poly(tetramethylene oxide) glycol, and the equivalent ratio of isocyanate from component A to hydroxyl from component B is 0.8 to 2.0; (2) mixing component A and component B in a desired ratio to form the adhesive; (3) applying an adhesive to at least one substrate; (4) contacting a second substrate with the adhesive; and (5) Curing the adhesive The present invention provides a method comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present inventors have discovered that by using the two-component polyurethane adhesive of the present invention, excellent thermal conductivity, high bond strength, and excellent elongation can be achieved.
[0009] Definitions and Abbreviations MDI 4,4'-methylenebis(phenylisocyanate) HDI Hexamethylene Diisocyanate IPDI Isophorone Diisocyanate PU Polyurethane SEC Size Exclusion Chromatography RH Relative Humidity CF Cohesive failure AF Adhesive failure
[0010] The equivalent weight and molecular weight are measured by gel permeation chromatography (GPC) using a Malvern Viscothek GPC max instrument. Tetrahydrofuran (THF) was used as the eluent, PL GEL MIXED D (Agilent, 300*7.5mm, 5μm) was used as the column, and MALVERN Viscotek TDA (combined refractive index viscometer and light scattering) was used as the detector.
[0011] Ingredient A Component A is (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter Includes.
[0012] At least one polyisocyanate (a1) The polyisocyanate is not particularly limited, but is preferably a polyisocyanate having 2 to 4 isocyanate functional groups.
[0013] Aliphatic and aromatic diisocyanates can be used, with aromatic being preferred.Suitable examples of diisocyanates include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene biscyclohexyl isocyanate (HMDI) (hydrogenated MDI), MDI (particularly 4,4'- and 4,2-MDI) and isophorone diisocyanate (IPDI), polycarbodiimide-modified MDI, with polycarbodiimide-modified MDI being particularly preferred.
[0014] In a preferred embodiment, the polyisocyanate is selected from polymeric MDI, polycarbodiimide modified MDI, and mixtures thereof.
[0015] In a preferred embodiment, the polyisocyanate is polycarbodiimide-modified 4,4'-methylenediphenyl diisocyanate. Particularly preferably, Component A contains 15 to 25% by weight of polycarbodiimide-modified 4,4'-methylenediphenyl diisocyanate based on the total weight of Component A.
[0016] The at least one polyisocyanate is preferably present in component A in an amount of 18 to 24% by weight, more preferably 19 to 22% by weight, and especially preferably 20% by weight, based on the total weight of component A.
[0017] The total polyisocyanate concentration in component A is preferably 18 to 24% by weight, more preferably 19 to 22% by weight, and particularly preferably 20% by weight, based on the total weight of component A.
[0018] Thermally conductive filler (a2), (b2) Component A and component B each contain 40 to 85% by weight of a thermally conductive filler based on the total weight of component A or component B.
[0019] The thermally conductive fillers used as a2 and b2 are not particularly limited. Suitable thermally conductive fillers have a thermal conductivity of more than 5 W / m°K, more than 10 W / m°K, or more than 15 W / m°K. Examples of thermally conductive fillers include alumina, alumina trihydrate or aluminum trihydroxide, silicon carbide, boron nitride, diamond, and graphite, or mixtures thereof. Particularly preferred embodiments are aluminum trihydroxide (ATH) and aluminum oxide, with ATH being most preferred. The thermally conductive fillers may be surface-treated or untreated.
[0020] In a preferred embodiment, the thermally conductive filler has a D of about 3 or greater. 90 / D 50 Particularly preferably, the thermally conductive filler has a broad particle size distribution characterized by a D ratio of about 3 or more. 90 / D 50ATH or aluminum oxide having a broad particle size distribution characterized by the ratio, most preferably ATH.
[0021] Similarly, thermally conductive fillers having a bimodal particle size distribution are also preferred. 90 / D 50 The ratio is about 3 or more, more preferably about 5 or more, and even more preferably about 9 or more. For example, D of 5 to 20 microns 50 and D of 70 to 90 microns 90 , especially D of 7 to 9 microns 50 and D of 78 to 82 microns 90 The particle size can be determined using laser diffraction. For ATH, a suitable solvent is deionized water with a dispersing aid such as Na4P2O7x10H2O, preferably at 1 g / l. Preferred are aluminum oxide and ATH, especially ATH, with a bimodal distribution. In a preferred embodiment, the thermally conductive filler has a D of about 3 or more, more preferably about 5 or more, and especially preferably about 9 or more. 90 / D 50 It is an ATH having the above.
[0022] In a preferred embodiment, the thermally conductive filler is a bimodal aluminum trihydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7×10H2O, preferably at 1 g / l): D 10 (microns) 0.5 D 50 (microns) 8 D 90 (microns) 80
[0023] The thermally conductive filler is present in the final adhesive at a concentration of 65-85% by weight based on the total weight of the adhesive, and preferably at a concentration that results in a thermal conductivity of 1.1 W / mK or greater after curing at 23° C. for 7 days.
[0024] When components A and B are mixed in a volume ratio of 1:1, the preferred concentration of the thermally conductive filler in component A is 60 to 85% by weight, more preferably 62 to 70% by weight, based on the total weight of component A.
[0025] When components A and B are mixed in a volume ratio of 1:1, the preferred concentration of the thermally conductive filler in component B is 60 to 85% by weight, more preferably 63 to 72% by weight, based on the total weight of component B.
[0026] In a preferred embodiment, component A is D 90 / D 50 The component A contains 60 to 85 wt %, more preferably 62 to 70 wt %, of ATH having a molecular weight of about 3 or more, more preferably about 5 or more, and particularly preferably about 9 or more, based on the total weight of the component A.
[0027] In a preferred embodiment, component B is D 90 / D 50 The component B contains 60 to 85% by weight, more preferably 62 to 70% by weight, of ATH having a molecular weight of about 3 or more, more preferably about 5 or more, and particularly preferably about 9 or more, based on the total weight of the component B.
[0028] Polyether polyols (a3, b1) The at least one polyol is preferably a diol, triol or tetraol. Preferably, it is a diol, triol or a mixture of diols and triols, with mixtures of diols and triols being particularly preferred.
[0029] Polyether polyols are well known in the art and include, for example, polyoxyethylene, polyoxypropylene, polyoxybutylene, and polytetramethylene ether diols and triols, which can be prepared, for example, by reacting unsubstituted or halogen- or aromatic-substituted ethylene oxide or propylene oxide with an initiator compound containing two or more active hydrogen groups, such as water, ammonia, polyhydric alcohol, or amine. In general, polyether polyols can be prepared by polymerizing alkylene oxides in the presence of an active hydrogen-containing initiator compound. Preferred polyether polyols contain one or more alkylene oxide units in the backbone of the polyol. Preferred alkylene oxide units are ethylene oxide, propylene oxide, butylene oxide, and mixtures thereof. Preferably, the polyol contains propylene oxide units, ethylene oxide units, or mixtures thereof. In embodiments in which a mixture of alkylene oxide units is contained in the polyol, the different units can be arranged randomly or in blocks of each alkylene oxide. In a preferred embodiment, the polyol comprises a propylene oxide chain. In a preferred embodiment, the polyether polyol is a mixture of polyether diols and polyether triols. Preferably, the polyether polyol or mixture has a functionality of at least about 2.0, preferably about 2.0 to 3.0 or more, such as 3.5, 4.0 or more. Preferably, the equivalent weight of the polyether polyol mixture is 45 to 1,200 g / eq.
[0030] More specific examples of polyether polyols include the following: 1. Difunctional polyols (diols), such as poly(alkylene oxide) diols, in which the alkylene groups are C2 to C4, are particularly preferred, particularly poly(propylene oxide) diols, such as poly(ethylene oxide) diol, poly(propylene oxide) diol, poly(butylene oxide) diol and poly(tetramethylene oxide) diol. In a particularly preferred embodiment, the polyether polyol comprises a nominally difunctional poly(propylene oxide) having an equivalent weight of 80 to 2,500, more preferably 200 to 1,500. 2. Trifunctional polyols (triols), such as alkylene oxides initiated with trifunctional polyols, such as trimethylolpropane, where the alkylene groups are C2 to C4, especially propylene oxide, such as those based on ethylene oxide, propylene oxide, butylene oxide, tetramethylene oxide and butylene oxide. In a particularly preferred embodiment, the polyether polyol comprises a nominally trifunctional poly(propylene oxide) of equivalent weight between 80 and 2,500 g / eq, more preferably between 80 and 90 g / eq, the polymers may or may not be capped with ethylene oxide to modify reactivity. 3. Mixtures of 1 and 2. Particularly preferred are mixtures of 1 and 2, and even more particularly preferred are mixtures of a) a nominally difunctional poly(propylene oxide) having an equivalent weight of 100 to 2,500, more preferably 200 to 1,500, and especially preferably 200 to 1,100, and b) a nominally trifunctional poly(propylene oxide) having an equivalent weight of 80 to 90.
[0031] In a particularly preferred embodiment, the at least one polyol comprises a mixture of propylene oxide-based diols and triols.
[0032] In a preferred embodiment, the at least one polyol comprises a mixture of two or more diols and one or more triols. Particularly preferred is a mixture of two or more polypropylene oxide-based diols and polypropylene oxide-based triols.
[0033] In a preferred embodiment, the at least one polyol in component B includes: Poly(propylene oxide) diol with an equivalent weight of 1,000 g / eq, Poly(propylene oxide) diol with an equivalent weight of 200-220 g / eq, ·Poly(propylene oxide) triol with an equivalent weight of 80-90g / eq.
[0034] In another preferred embodiment, the at least one polyol in component B includes: about 1-3 wt. %, based on the total weight of component B, of a poly(propylene oxide) diol having an equivalent weight of 1,000 g / eq; 8 to 10% by weight, based on the total weight of component B, of a poly(propylene oxide) diol having an equivalent weight of 200 to 220 g / eq, · 1.5 to 4 weight percent, based on the total weight of component B, of a poly(propylene oxide) triol having an equivalent weight of 80 to 90 g / eq.
[0035] Component A and / or Component B contains poly(tetramethylene oxide) diol (PTMEG) as a polyol. PTMEG preferably has a molecular weight of 200 to 2000 Da, preferably 500 to 1500 Da, more preferably 1000 Da.
[0036] In a preferred embodiment, PTMEG is present in component B. In a particularly preferred embodiment, PTMEG is present in component B at 1 to 20% by weight, preferably 5 to 20% by weight, more preferably 10 to 15% by weight, based on the total weight of component B.
[0037] In a preferred embodiment, PTMEG is present only in component B. In a particularly preferred embodiment, PTMEG is present only in component B at 1 to 20% by weight, preferably 5 to 20% by weight, more preferably 10 to 15% by weight, based on the total weight of component B.
[0038] In a preferred embodiment, PTMEG has a molecular weight of 1,000 Da and is present in Component B at 10-15 wt. %, more preferably 11-12 wt. %, based on the total weight of Component B.
[0039] In a preferred embodiment, PTMEG has a molecular weight of 1,000 Da and is present exclusively in Component B at 10-15 wt. %, more preferably 11-12 wt. %, based on the total weight of Component B.
[0040] In a preferred embodiment, PTMEG is present in the final adhesive (a mixture of components A and B) at 5-7.5% by weight, more preferably 5-6% by weight, based on the total weight of the adhesive.
[0041] In a preferred embodiment, component B is Poly(propylene oxide) diol with an equivalent weight of 1,000 g / eq, Poly(propylene oxide) diol with an equivalent weight of 200-220 g / eq, Poly(propylene oxide) triol with an equivalent weight of 80-90 g / eq, and PTMEG diol with an equivalent weight of 250 to 1,000 g / eq, preferably 500 g / eq Includes.
[0042] In another preferred embodiment, component B is about 1-3 wt. %, based on the total weight of component B, of a poly(propylene oxide) diol having an equivalent weight of 1,000 g / eq; 8 to 10% by weight, based on the total weight of component B, of a poly(propylene oxide) diol having an equivalent weight of 200 to 220 g / eq, 1.5 to 4 wt. %, based on the total weight of component B, of a poly(propylene oxide) triol having an equivalent weight of 80 to 90 g / eq, and 5 to 15% by weight, more preferably 10 to 12% by weight, of PTMEG diol having an equivalent weight of 250 to 1,000 g / eq, more preferably 500 g / eq, based on the total weight of component B Includes.
[0043] In another preferred embodiment, component B is about 1-3 wt. %, based on the total weight of component B, of a poly(propylene oxide) diol having an equivalent weight of 1,000 g / eq; 8 to 10% by weight, based on the total weight of component B, of a poly(propylene oxide) diol having an equivalent weight of 200 to 220 g / eq, 1.5 to 4 wt. %, based on the total weight of component B, of a poly(propylene oxide) triol having an equivalent weight of 80 to 90 g / eq, and 10-12% by weight, based on the total weight of component B, of PTMEG diol having an equivalent weight of 500 g / eq. Includes.
[0044] Silane adhesion promoter (a4, b4) A silane adhesion promoter is any molecule that has a hydrolyzable silane moiety attached to a functional group selected from an amino group, a mercapto group, and an epoxy group. The hydrolyzable silane moiety can be derived from an alkoxysilane moiety.
[0045] The alkoxy group of the alkoxysilane moiety is preferably selected from C1-C4 alkoxy, namely methoxy, ethoxy, propoxy and butoxy, in a preferred embodiment the alkoxy group is methoxy or ethoxy, in particular methoxy.
[0046] In a preferred embodiment, the functional group is amino and the trialkoxysilane moiety is trimethoxysilane.
[0047] In a preferred embodiment, the functional group is mercapto and the trialkoxysilane moiety is trimethoxysilane.
[0048] In a preferred embodiment, the functional group is epoxy and the trialkoxysilane moiety is trimethoxysilane.
[0049] Examples of silane adhesion promoters include:
[0050] Aminosilane Diethylaminomethyltrimethoxysilane, diethylaminomethylmethyldiethoxysilane, diethylaminomethyltriethoxysilane, piperazinylpropylmethyldimethoxysilane, diethylenetriaminopropylmethyldimethoxysilane, aminoethylaminopropyltriethoxysilane, bis-[(3-triethoxysilyl)propyl]amine, diethylaminomethyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, aminopropylmethyldimethoxysilane, bis-(trimethoxysilylpropyl)amine, gamma-aminopropyltrimethoxysilane, 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine, N-β-(aminoethyl)-γ -aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, phenylaminopropyltrimethoxysilane, N-ethyl-3-trimethoxysilyl-2-methylpropanamine, aminoethylaminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 1-propanamine, 3-(triethoxysilyl), N-(n-butyl)-3-aminopropyltrimethoxysilane, bis-(trimethoxysilanepropyl)amine, in particular 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine, are preferred.
[0051] Epoxy Silane 2-(3,4-epoxycyclohexyl)-ethyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, (epoxypropoxypropyl)methyldiethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, gamma-glycidoxypropyltrimethoxysilane, beta-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, gamma-glycidoxypropyltriethoxysilane, 3-glycidyloxypropyltriethoxysilane, 9-[2-(2-methoxyethoxy)ethoxy]-9-[3-(oxiranylmethoxy)propyl]-2,5,8,10,13,16-hexaoxa-9-silaheptadecane.
[0052] Mercaptosilane Mercaptomethyltriethoxysilane, mercaptomethyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, mercaptopropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, 3-(triethoxysilyl)propanethiol, γ-mercaptopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane.
[0053] In a preferred embodiment, the silane adhesion promoter is an aminosilane.
[0054] In another preferred embodiment, the silane adhesion promoter is 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine.
[0055] In a preferred embodiment, the silane adhesion promoter is present in component A.
[0056] In another preferred embodiment, the silane adhesion promoter is present in component B.
[0057] In another preferred embodiment, the silane adhesion promoter is present only in component A.
[0058] In a particularly preferred embodiment, the silane adhesion promoter is 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine and is present only in component A.
[0059] When used, the silane adhesion promoter is preferably present in Component A and / or Component B at 0.1 to 4 wt %, preferably 0.5 to 3 wt %, more preferably 1.5 to 3 wt %, based on the total weight of each component.
[0060] In a preferred embodiment, the silane adhesion promoter is present in Component A at 0.1 to 4 wt. %, preferably 0.5 to 3%, and more preferably 1.5 to 3 wt. %, based on the total weight of Component A.
[0061] In a particularly preferred embodiment, the silane adhesion promoter is 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine and is present in Component A at 0.1 to 4 wt. %, preferably 0.5 to 3%, and more preferably 1.5 to 3 wt. %, based on the total weight of Component A.
[0062] Optional Ingredients for Component A In addition to the thermally conductive filler, component A may additionally comprise fillers such as talc, fumed silica, carbon black and mixtures thereof. In a preferred embodiment, component A comprises fumed silica. In another preferred embodiment, component A comprises carbon black. In a particularly preferred embodiment, component A comprises fumed silica and carbon black.
[0063] Component A may comprise a polyol, such as any of the polyols described above. In a particularly preferred embodiment, component A comprises a diol having a molecular weight of 1,000 to 2,500 Da, more preferably 2,000 Da.
[0064] When present, the polyol in Component A is preferably present at 5 to 15 weight percent, more preferably 9 to 12 weight percent, based on the total weight of Component A.
[0065] In a particularly preferred embodiment, component A comprises 9 to 12 wt. % based on the total weight of component A of a propylene glycol initiated homopolymer diol having a molecular weight of 2000, an average equivalent weight of 1000 g / eq, and an average OH number of 56 mg KOH / g.
[0066] Component B Component B is (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter Includes.
[0067] Polyether polyol The polyether polyol used in component B can be selected from any of those listed above.
[0068] In a preferred embodiment, the polyether polyol (b1) is selected from poly(propylene oxide)-based diols and triols.
[0069] In another preferred embodiment, the polyether polyol (b1) is poly(propylene oxide) diol, poly(propylene oxide) triol, Poly(tetramethylene oxide) diol, and Mixtures of these The polyol is selected from the group consisting of
[0070] In another preferred embodiment, the polyether polyol (b1) is a poly(propylene oxide) polyol diol having an average molecular weight of 425 g / mole; a poly(propylene oxide) polyol triol having an average molecular weight of 250 g / mole; Poly(tetramethylene oxide) diol, and Mixtures of these The polyol is selected from the group consisting of
[0071] In another preferred embodiment, the polyether polyol (b1) is a poly(propylene oxide) polyol diol having an average molecular weight of 425 g / mol, an average equivalent weight of 215.7 g / eq, and an average OH number of 259 mg KOH / g; Poly(propylene oxide) polyol triol having an average molecular weight of 250, an average equivalent weight of 84.9 g / eq, and an average OH number of 660 mg KOH / g; Poly(tetramethylene oxide) diol, and Mixtures of these The polyol is selected from the group consisting of
[0072] In a preferred embodiment, component B comprises a poly(tetramethylene oxide) diol having a molecular weight of 200 to 2,000 Da, more preferably 1,000 Da.
[0073] In another preferred embodiment, the polyether polyol comprises 1,4-butanediol.
[0074] In a particularly preferred embodiment, the polyether polyol is poly(propylene oxide) diol, poly(propylene oxide) triol, Poly(tetramethylene oxide) diol, 1,4-butanediol, and Mixtures of these The polyol is selected from the group consisting of
[0075] The total content of polyether polyols in Component B is preferably from 20 to 30% by weight, more preferably from 24 to 28% by weight, and particularly preferably from 25 to 27% by weight, based on the total weight of Component B.
[0076] Poly(tetramethylene oxide) diol preferably comprises, on a weight percent basis, 3 to 55%, preferably 20 to 55%, more preferably 30 to 50%, and especially preferably 40 to 48% of the total polyol content of Component B.
[0077] The poly(tetramethylene oxide) diol is preferably present in Component B at 1 to 20% by weight, preferably 5 to 20% by weight, more preferably 7 to 15% by weight, and especially preferably 8 to 12% by weight, based on the total weight of Component B.
[0078] In a preferred embodiment, component B is poly(propylene oxide) diol, poly(propylene oxide) triol, Poly(tetramethylene oxide) diol having a molecular weight of 1,000 Da, and Mixtures of these Includes.
[0079] In another preferred embodiment, the polyether polyol (b1) is a poly(propylene oxide) polyol diol having an average molecular weight of 425 g / mol; Poly(propylene oxide) polyol triol having an average molecular weight of 250 g / mol; Poly(tetramethylene oxide) diol having a molecular weight of 1,000 Da, and Mixtures of these The polyol is selected from the group consisting of
[0080] In another preferred embodiment, the polyether polyol (b1) is Poly(propylene oxide) polyol diol with average molecular weight of 425 g / mol, average equivalent weight of 215.7 g / eq, and average OH number of 259 mg KOH / g; Poly(propylene oxide) polyol triol having an average molecular weight of 250, an average equivalent weight of 84.9 g / eq, and an average OH number of 660 mg KOH / g; Poly(tetramethylene oxide) diol with a molecular weight of 1,000 Da, and Mixtures of these The polyol is selected from the group consisting of
[0081] In a preferred embodiment, component B is poly(propylene oxide) diol, poly(propylene oxide) triol, 1,4-butanediol, Poly(tetramethylene oxide) diol having a molecular weight of 1,000 Da, and Mixtures of these Includes.
[0082] In another preferred embodiment, the polyether polyol (b1) is a poly(propylene oxide) polyol diol having an average molecular weight of 425 g / mole; a poly(propylene oxide) polyol triol having an average molecular weight of 250 g / mole; 1,4-butanediol, Poly(tetramethylene oxide) diol having a molecular weight of 1,000 Da, and Mixtures of these The polyol is selected from the group consisting of
[0083] In another preferred embodiment, the polyether polyol (b1) is Poly(propylene oxide) polyol diol with average molecular weight of 425 g / mol, average equivalent weight of 215.7 g / eq, and average OH number of 259 mg KOH / g; Poly(propylene oxide) polyol triol having an average molecular weight of 250, an average equivalent weight of 84.9 g / eq, and an average OH number of 660 mg KOH / g; 1,4-butanediol, Poly(tetramethylene oxide) diol with a molecular weight of 1,000 Da, and Mixtures of these The polyol is selected from the group consisting of
[0084] Catalyst (b3) Component B comprises a catalyst capable of catalyzing the reaction of NCO functional groups with OH functional groups.
[0085] Examples of such catalysts include tertiary amine catalysts, organometallic catalysts such as bismuth catalysts, alkyltin carboxylates, oxides and tin mercaptides.
[0086] Specific examples of tertiary amine catalysts include N-methylmorpholine, N-methylimidazole, triethylenediamine, bis-(2-dimethylaminoethyl)-ether, 1,4-diazabicyclo[2.2.2]octane (DABCO), dimethylcyclohexylamine, dimethylethanolamine, 2,2-dimorpholinyl diethyl ether (DMDEE), N,N,N-dimethylaminopropylhexahydrotriazine, dimethyltetrahydropyrimidine, tetramethylethylenediamine, dimethylcyclohexylamine, 2,2-N,N-benzyldimethylamine, Examples of the diamine include dimethylethanolamine, dimethylaminopropylamine, pentadimethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N',N'-trimethylaminoethylpiperazine, 1,1'-[[3-(dimethylamino)propyl]imino]bispropan-2-ol, 1,3,5-tris[3-(dimethylamino)propyl]hexahydro-1,3,5-triazine, N-N-dimethyldipropylenetriamine, and N,N,N'-trimethylaminoethylethanolamine, with DMDEE being particularly preferred.
[0087] When an organometallic catalyst is used, it is any organometallic catalyst capable of catalyzing the reaction between an isocyanate and a functional group having at least one reactive hydrogen. Examples include bismuth catalysts, metal carboxylates, such as tin carboxylates, zinc carboxylates, etc. Metal alkanoates include stannous octoate, bismuth octoate, or bismuth neodecanoate. Preferably, the at least one organometallic catalyst is a bismuth catalyst or an organotin catalyst. Examples include dibutyltin dilaurate, dimethyltin dineodecanoate, dimethyltin mercaptide, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin mercaptide, dibutyltin bis(2-ethylhexylthioglycolate), dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin mercaptide, dioctyltin dioctoate, dioctyltin dineodecanoate, dioctyltin dilaurate. In a particularly preferred embodiment, this is a tin catalyst, particularly preferably dioctyltin mercaptide.
[0088] The catalyst is preferably used in an amount of 0.001 to 0.12% by weight, more preferably 0.01 to 0.1% by weight, based on the total weight of component B.
[0089] In a preferred embodiment, the catalyst is dioctyltin mercaptide, which is used at 0.03 to 0.07% by weight, based on the total weight of component B.
[0090] Optional Ingredients for Component B In addition to the thermally conductive filler, component B may additionally contain fillers such as talc, fumed silica, carbon black, zeolites, and mixtures thereof.
[0091] In a preferred embodiment, component B comprises fumed silica.
[0092] In another preferred embodiment, component B comprises carbon black.
[0093] In another preferred embodiment, component B comprises a zeolite.
[0094] In a particularly preferred embodiment, component B comprises fumed silica and carbon black, more preferably component B comprises fumed silica, carbon black and zeolite.
[0095] Component B may optionally contain a polyisocyanate in an amount that, when reacted with the polyol portion of Component B, results in an excess of residual OH groups.
[0096] In a preferred embodiment, component B comprises MDI, polycarbodiimide modified MDI.
[0097] When Component B includes a polyisocyanate, it is preferably present at 0.4 to 2 wt. %, more preferably 1 to 1.5 wt. %, based on the total weight of Component B.
[0098] In a preferred embodiment, component B contains 0.4 to 2 wt %, more preferably 1 to 1.5 wt %, of polycarbodiimide-modified MDI based on the total weight of component B.
[0099] Ratio of NCO groups to OH groups The equivalent ratio of the isocyanate derived from Component A to the hydroxyl derived from Component B is 0.8 to 2.0, preferably 0.9 to 1.5, and more preferably 1.0 to 1.3.
[0100] Manufacturing method The adhesive composition of the present invention is prepared by mixing the ingredients of each component separately, preferably under inert and dry conditions and / or under vacuum, until a homogenous mixture is obtained. After components A and B are each prepared, they are stored in separate containers until use.
[0101] How to use In one aspect, the present invention provides a method for bonding two or more substrates, comprising the steps of: (1) providing a thermally conductive two-component polyurethane adhesive composition, the thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein at least one of the polyether polyols in component A and component B is poly(tetramethylene oxide) glycol; (2) mixing component A and component B in a desired ratio to form the adhesive; (3) applying an adhesive to at least one substrate; (4) contacting a second substrate with the adhesive; and (5) Curing the adhesive The present invention provides a method comprising:
[0102] As noted above, a preferred method of providing the adhesive components of the present invention is in an airtight container, such as a hermetically sealed tube, which is opened immediately prior to use.
[0103] The adhesive composition of the present invention may be applied by any application method, such as, for example, spreading, applying through a nozzle, either manually or with robotic equipment.
[0104] In a preferred embodiment, one or both of the first and second substrates are selected from metal, coated metal, glass, glass with primer, glass with enamel coating, plastic (such as talc or glass-filled polypropylene), polycarbonate, sheet molding compound, composite material (such as carbon fiber reinforced epoxy, glass fiber reinforced polyamide). In a preferred embodiment, at least one of the first and second substrates is a metal, particularly steel or aluminum, particularly preferably e-coated steel, e-coated aluminum. In a particularly preferred embodiment, both substrates are e-coated steel.
[0105] Curing begins immediately after components A and B are mixed. Typical curing conditions are 3-7 days at 23°C.
[0106] Effect of the Invention The adhesives of the invention exhibit a thermal conductivity, after curing at 23° C. for 7 days, of at least 1 W / mK, more preferably at least 1.12 W / mK, and especially preferably at least 1.16 W / mK, as measured according to ASTM D5470.
[0107] The adhesives of the present invention preferably exhibit a lap shear elongation at maximum stress after curing at 23° C. for 7 days, as measured according to SAE J1529 method, of 50% or more, more preferably 60% or more, and especially preferably 64% or more.
[0108] For tensile strength, two-part adhesive samples were dispensed through a spiral static mixer between two sheets of release paper and then pressed to form 3 mm thick circular plaques. The circular plaques were cured for 7 days at 23°C and 50% relative humidity (RH). Three specimens were cut from the cured sample plaques using ASTM D412 Die C and tested at a pull rate of 50 mm per minute using an Instron Model 5969 tester. Tensile strength (MPa) was calculated as the peak force (Newtons) multiplied by the cross-sectional area (mm 2) and elongation was determined at the specimen break point, all in accordance with ASTM D412. Tensile strength and elongation results for adhesive samples were reported from an average of three specimens.
[0109] The tensile strength is preferably greater than 4 MPa, more preferably greater than 5 MPa, particularly preferably greater than 6 MPa. The elongation is preferably greater than 15% at break, more preferably greater than 25% at break, particularly preferably greater than 30% at break.
[0110] For impact peel measurements, specimens were prepared using E-coated (ED6100C) steel coupons measuring 25.4 mm wide, 101.6 mm long, and 0.8 mm thick. 2K adhesive samples were dispensed from a spiral static mixer onto one end of the E-coated steel coupon, which was then overlapped with the same E-coated steel coupon to create a 30 mm adhesive overlap and 1.2 mm bondline thickness at the end of the specimen. Impact peel specimens were cured at 23°C and 50% relative humidity for 7 days or as specified. The cured impact specimens were pre-bent into a V-shape at the other unbonded end and then tested with a normal impact mass of 23.7 kg at a speed of 2.4 m / s. Reported impact peel strengths (Newtons / mm) are averaged over the area between 45% and 90% of the displacement to failure, all in accordance with ISO 11343 [2003 04 01]. Typically, at least three specimens were tested and averaged for the adhesive sample.
[0111] The impact peel strength is preferably greater than 8 N / mm, more preferably greater than 10 N / mm, particularly preferably greater than 12 N / mm, and most preferably greater than 15 N / mm. The impact peel failure is preferably greater than 85% cohesive failure (CF), more preferably greater than 95% CF, and most preferably 100% CF.
[0112] The adhesives of the present invention preferably exhibit a lap shear failure mode of 85% or greater cohesive failure, more preferably 95% or greater cohesive failure, and most preferably 100% cohesive failure after 7 days cure at 23° C. when measured according to SAE J1529 test procedure.
[0113] The press flow viscosity of component A or B is preferably greater than 5 seconds / 20 grams, more preferably greater than 9 seconds / 20 grams, particularly preferably greater than 12 seconds / 20 grams. The press flow viscosity of component A or B is preferably less than 60 seconds / 20 grams, more preferably less than 45 seconds / 20 grams, particularly preferably greater than 35 seconds / 20 grams. All values refer to press flow viscosities determined by recording the time (in seconds) required for 20 grams of the adhesive sample component to pass through a 2.64 mm orifice under conditions of 25° C. and 310 kPa applied pressure.
[0114] Brookfield viscosity is DV-E type Brookfield Measure using a viscometer or equivalent according to the procedure described in U.S. Patent No. 5,922,809, column 12, lines 38-49. Freshly prepared adhesive components (Component A or Component B) are first conditioned for at least 2 hours at 40° C. Tests are then performed at 40° C. using RV spindle #7 at a speed of 6 revolutions per second unless otherwise specified.
[0115] The Brookfield viscosity of component A or B at 40° C. is preferably greater than 50,000 centipoise, more preferably greater than 100,000 centipoise, and particularly preferably greater than 160,000 centipoise. The Brookfield viscosity of component A or B at 40° C. is preferably less than 1,000,000 centipoise, more preferably less than 700,000 centipoise, and particularly preferably less than 550,000 centipoise.
[0116] The electrical resistivity is measured as follows: Two copper strips (50 mm long, 12 mm wide) are placed parallel, 50 mm apart, on a non-conductive surface such as cardboard. An adhesive bead (approximately 4 mm in diameter) is dispensed perpendicularly onto the two copper strips through a static mixer, passing through the center of the strips. The bead is cured for 7 days (or a predefined time) at 23° C. and 50% relative humidity. The resistivity of the bead is determined using an electrical multimeter by contacting its two probes to the two copper strips. The electrical resistivity is preferably greater than 300,000 ohms, more preferably greater than 500,000 ohms, and especially preferably greater than 1×10 6 ohms, most preferably 2×10 6 It is super ohms.
[0117] Purpose The properties of the adhesives of the present invention make them particularly suitable for applications requiring good adhesion, good elongation and good thermal conductivity.
[0118] In preferred embodiments, the adhesives of the present invention are used to bond battery assemblies, bond battery cells together, bond battery cells to modules, or bond battery cells to cooling plates.
[0119] Particularly preferred embodiments The following are particularly preferred embodiments of the adhesive composition of the present invention. 1. A thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein at least one of the polyether polyols in component A and component B is poly(tetramethylene oxide) glycol, and the equivalent ratio of the isocyanate derived from component A to the hydroxyl derived from component B is 0.8 to 2.0. 2. A method for bonding two or more substrates, comprising the steps of: (1) providing a thermally conductive two-component polyurethane adhesive composition, the thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B at least one of the polyether polyols in component A and component B is poly(tetramethylene oxide) glycol, and the equivalent ratio of isocyanate from component A to hydroxyl from component B is 0.8 to 2.0; (2) mixing component A and component B in a desired ratio to form the adhesive; (3) applying an adhesive to at least one substrate; (4) contacting a second substrate with the adhesive; and (5) Curing the adhesive The method includes: 3. A thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol comprising poly(tetramethylene oxide) glycol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein the equivalent ratio of the isocyanate derived from component A to the hydroxyl derived from component B is 0.8 to 2.0. 4. A thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate containing polycarbodiimide-modified MDI; (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol comprising poly(tetramethylene oxide) glycol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein the equivalent ratio of the isocyanate derived from component A to the hydroxyl derived from component B is 0.8 to 2.0. 5. A thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol comprising at least 8 wt. % poly(tetramethylene oxide) glycol, based on the total weight of component B; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein the equivalent ratio of the isocyanate derived from component A to the hydroxyl derived from component B is 0.8 to 2.0. 6. A thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate containing polycarbodiimide-modified MDI; (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising: (B) a polyol component, component B, (b1) at least one polyether polyol comprising at least 8 wt. % poly(tetramethylene oxide) glycol, based on the total weight of component B; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein the equivalent ratio of the isocyanate derived from component A to the hydroxyl derived from component B is 0.8 to 2.0. 7. Any one of the preceding embodiments, wherein the equivalent ratio of isocyanate from Component A to hydroxyl from Component B is 0.9 to 1.5. 8. Any one of the preceding embodiments, wherein the equivalent ratio of isocyanate from Component A to hydroxyl from Component B is 1.0 to 1.3. 9. Any one of embodiments 1-8, wherein component B comprises poly(tetramethylene oxide) glycol. 10. Any one of embodiments 1-9, wherein component A comprises poly(tetramethylene oxide) glycol. 11. Any one of embodiments 1-10, wherein component A and component B comprise poly(tetramethylene oxide) glycol. 12. Any one of embodiments 1 to 11, wherein component B comprises 1 to 20 wt. %, preferably 5 to 20 wt. %, and more preferably 10 to 15 wt. % of poly(tetramethylene oxide) glycol, based on the total weight of component B. 13. Any one of embodiments 1-12, wherein the poly(tetramethylene oxide) glycol has a molecular weight of 200 to 2,000 Da. 14. Any one of embodiments 1-13, wherein the poly(tetramethylene oxide) glycol is present in the adhesive at 1-7.5 wt %, preferably 5-7.5 wt %, and more preferably 5-6 wt %, based on the total weight of the adhesive. 15. Any one of embodiments 1-14, wherein component A comprises a silane adhesion promoter. 16. Any one of embodiments 1-15, wherein component A comprises an aminosilane adhesion promoter. 17. Any one of embodiments 1-16, wherein Component A comprises 0.1 to 4 wt. %, preferably 0.5 to 3 wt. %, and more preferably 1.5 to 3 wt. % of a silane adhesion promoter, based on the total weight of Component A. 18. Any one of embodiments 1-17, wherein the adhesive comprises 0.1-2 wt. %, preferably 0.5-2 wt. %, and more preferably 0.75-1.5 wt. % of a silane adhesion promoter, based on the total weight of the adhesive. 19. Any one of embodiments 1-18, wherein the silane adhesion promoter is 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine. 20. Any one of embodiments 1-19, wherein Component B comprises 5-20 wt. %, more preferably 10-15 wt. %, of poly(tetramethylene oxide) glycol, based on the total weight of Component B, and Component A comprises 0.1-4 wt. %, preferably 0.5-3 wt. %, more preferably 1.5-3 wt. %, of a silane adhesion promoter, based on the total weight of Component A. 21. Any one of embodiments 1-20, wherein component B comprises a polyether polyol selected from diols, triols, and mixtures thereof. 22. Component B is poly(propylene oxide) diol, Poly(propylene oxide) triol, and Poly(tetramethylene oxide) diol Any one of embodiments 1 to 21, including: 23. Component B is poly(propylene oxide) diol having an average equivalent weight of 900 to 1,100 g / eq; a poly(propylene oxide) diol having an average equivalent weight of 190 to 230 g / eq; a poly(propylene oxide) triol having an average equivalent weight of 70 to 100 g / eq; and Poly(tetramethylene oxide) diol Any one of embodiments 1 to 22, including: 24. Component B is poly(propylene oxide) diol having an average equivalent weight of 1,000 g / eq; poly(propylene oxide) diol having an average equivalent weight of 215.7 g / eq; a poly(propylene oxide) triol having an average equivalent weight of 84.9 g / eq, and Poly(tetramethylene oxide) diol Any one of embodiments 1 to 23, including: 25. Component B, based on the total weight of component B, 8 to 14 weight percent of poly(propylene oxide) diol; 1.5 to 5 weight percent poly(propylene oxide) triol, and 5-15% by weight of poly(tetramethylene oxide) diol Any one of embodiments 1 to 24, including: 26. Component B, based on the total weight of component B, 1 to 4 weight percent of a poly(propylene oxide) diol having an average equivalent weight of 900 to 1,100 g / eq; 7 to 14 wt. % of a poly(propylene oxide) diol having an average equivalent weight of 190 to 230 g / eq; 1.5 to 3 wt. % of a poly(propylene oxide) triol having an average equivalent weight of 70 to 100 g / eq, and 5-15% by weight of poly(tetramethylene oxide) diol Any one of embodiments 1 to 25, including: 27. Component B, based on the total weight of component B, 1 to 4 weight percent of a poly(propylene oxide) diol having an average equivalent weight of 1,000 g / eq; 7-14 wt. % of a poly(propylene oxide) diol having an average equivalent weight of 215.7 g / eq; 1.5 to 3 wt. % of a poly(propylene oxide) triol having an average equivalent weight of 84.9 g / eq, and 5-15% by weight of poly(tetramethylene oxide) diol Any one of embodiments 1 to 26, including: 28. Any one of embodiments 1-27, wherein component B comprises 1,4-butanediol. 29. Any one of embodiments 1-28, wherein component B comprises 0.5 to 2.5% by weight of 1,4-butanediol, based on the total weight of component B. 30. Any one of the preceding embodiments, wherein component A comprises a polymeric MDI that contains MDI. 31. Any one of embodiments 1-30, wherein component A comprises a polycarbodiimide-modified 4,4'-methylene diphenyl diisocyanate. 32. Any one of embodiments 1 to 31, wherein component A comprises 8 to 25 weight percent of polycarbodiimide-modified 4,4'-methylene diphenyl diisocyanate, based on the total weight of component B. 33. Any one of embodiments 1-32, wherein the catalyst (b3) is selected from tertiary amine catalysts, organometallic catalysts, such as bismuth catalysts, alkyltin carboxylates, oxides, and tin mercaptides. 34. Catalyst (b3) is N-methylmorpholine, N-methylimidazole, triethylenediamine, bis-(2-dimethylaminoethyl)-ether, 1,4-diazabicyclo[2.2.2]octane (DABCO), dimethylcyclohexylamine, dimethylethanolamine, 2,2-dimorpholinyl diethyl ether (DMDEE), N,N,N-dimethylaminopropyl hexahydrotriazine, dimethyltetrahydropyrimidine, tetramethylethylenediamine, dimethylcyclohexylamine, 2,2-N,N-benzyldimethylamine, dimethylethanolamine, di Any one of embodiments 1 to 33, wherein the diamine is selected from methylaminopropylamine, pentadimethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N',N'-trimethylaminoethylpiperazine, 1,1'-[[3-(dimethylamino)propyl]imino]bispropan-2-ol, 1,3,5-tris[3-(dimethylamino)propyl]hexahydro-1,3,5-triazine, N-N-dimethyldipropylenetriamine, N,N,N'-trimethylaminoethylethanolamine and mixtures thereof, with DMDEE being particularly preferred. 35. Any one of embodiments 1 to 34, wherein the catalyst (b3) is selected from dibutyltin dilaurate, dimethyltin dineodecanoate, dimethyltin mercaptide, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin mercaptide, dibutyltin bis(2-ethylhexylthioglycolate), dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin mercaptide, dioctyltin dioctoate, dioctyltin dineodecanoate, dioctyltin dilaurate, and mixtures thereof. 36. Any one of the preceding embodiments, wherein the catalyst (b3) is dioctyltin mercaptide. 37. Any one of the preceding embodiments, wherein the thermally conductive filler (a2, b2) is selected from fillers having a thermal conductivity greater than 5 W / m°K, greater than 10 W / m°K, or greater than 15 W / m°K. 38. Any one of embodiments 1 to 37, wherein the thermally conductive filler (a2, b2) is selected from alumina, surface-treated or untreated alumina trihydrate or aluminum trihydroxide, silicon carbide, boron nitride, diamond, graphite, and mixtures thereof. 39. Any one of embodiments 1-38, wherein the thermally conductive filler is aluminum trihydroxide (ATH) or aluminum oxide. 40. Any one of the preceding embodiments, wherein the thermally conductive filler is aluminum trihydroxide. 41.Thermal conductive filler has a D of about 3 or more. 90 / D 50 Any one of the preceding embodiments, having a broad particle size distribution characterized by the ratio: 42.Thermal conductive filler has a D of about 3 or more. 90 / D 50 Any one of embodiments 1-41, wherein the aluminum oxide or ATH has a broad particle size distribution characterized by the ratio, most preferably ATH. 43.Thermal conductive filler has a D of about 5 or more. 90 / D 50 Any one of embodiments 1 to 42, having a ratio. 44. Thermally conductive fillers have a D of about 9 or more. 90 / D 50 Any one of embodiments 1 to 43, having a ratio. 45. Thermally conductive filler is 5-20 microns D 50 and D of 70 to 90 microns 90 Any one of embodiments 1 to 44, comprising: 46. Thermally conductive filler has a D of 7 to 9 microns. 50 and D of 78 to 82 microns 90 Any one of embodiments 1 to 45, comprising: 47. Thermally conductive fillers have a D of about 3 or more. 90 / D 50 Any one of the preceding embodiments, wherein the ATH has a ratio of 48. Thermal conductivity is about 5 D or more. 90 / D 50 Any one of embodiments 1 to 47, wherein the ATH has a ratio. 49. Thermal conductivity is about 9 or more D 90 / D 50 Any one of embodiments 1 to 48, wherein the ATH has a ratio. 50. Any one of the preceding embodiments, wherein the thermally conductive filler is present in the adhesive at a concentration of 65 to 85% by weight, based on the total weight of the adhesive. 51. Any one of embodiments 1-50, wherein the adhesive has a thermal conductivity of 1.1 W / mK or greater after curing for 7 days at 23° C. EXAMPLES
[0120] [Table 1]
[0121] [Table 2]
[0122] Test Method Press Flow Viscosity Freshly prepared adhesive components (Component A or Component B) were first conditioned for at least 2 hours at 25° C. Press flow viscosity (seconds / 20 grams) was then determined by recording the time (in seconds) it took for 20 grams of an adhesive sample component to pass through a 2.64 mm orifice under an applied pressure of 310 kPa at 25° C., unless otherwise specified.
[0123] The press flow viscosity of component A or B is greater than 5 sec / 20 grams, preferably greater than 9 sec / 20 grams, more preferably greater than 12 sec / 20 grams. The press flow viscosity of component A or B is less than 60 sec / 20 grams, preferably less than 45 sec / 20 grams, more preferably greater than 35 sec / 20 grams.
[0124] Lap shear test Lap shear testing was performed according to the SAE J1529 test procedure described below. A round bead (approximately 4 mm in diameter) of the two-part adhesive composition was dispensed with an air gun through a static mixer and applied to a 25 mm x 100 mm e-coated (ED6100C) steel coupon along the width of the coupon at the end of the coupon. A second e-coated (ED6100C) steel coupon of the same size was immediately pressed onto the adhesive bead to a final height of 1 mm with an overlap of 12.7 mm of two-part adhesive composition therebetween. The prepared lap shear samples were cured at 23°C and 50% relative humidity for 7 days unless otherwise specified. The samples were then pulled at a rate of 1.27 mm / min using an Instron tester either immediately or after further exposure to the environment. Sample area (mm 2 The sample breaking load (Newtons) divided by the test load (MPa) gives the lap shear adhesive strength (MPa). The failure mode was evaluated as adhesive failure (AF), film failure (TF) and / or cohesive failure (CF). With AF, the cured bead can separate from the test substrate surface, while with CF, the separation occurs within the adhesive composition, and TF is a special case of CF where there is a thin film of cured adhesive composition remaining on the substrate after testing.
[0125] The lap shear strength at room temperature is greater than 4 MPa, preferably greater than 5 MPa, more preferably greater than 6 MPa. The lap shear elongation at maximum stress is greater than 50%, preferably greater than 55%, more preferably greater than 60%. The lap shear failure is greater than 85% CF, preferably greater than 95% CF, most preferably 100% CF.
[0126] Brookfield Viscosity Brookfield viscosity was measured using a DV-E Brookfield Viscometer or equivalent according to the procedure described in U.S. Patent No. 5,922,809, column 12, lines 38-49. Freshly prepared adhesive components (Component A or Component B) were first conditioned for at least 2 hours at 40° C. Testing was then performed at 40° C. using a RV spindle #7 at a speed of 6 revolutions per second unless otherwise specified.
[0127] The Brookfield viscosity of component A or B at 40° C. is greater than 50,000 centipoise, preferably greater than 100,000 centipoise, more preferably greater than 160,000 centipoise. The Brookfield viscosity of component A or B at 40° C. is less than 1,000,000 centipoise, preferably less than 700,000 centipoise, more preferably less than 550,000 centipoise.
[0128] Tensile and elongation properties The two-part adhesive samples were dispensed through a spiral static mixer between two sheets of release paper and then pressed to form 3 mm thick circular plaques. The circular plaques were cured for 7 days at 23°C and 50% relative humidity (RH). Three specimens were cut from the cured sample plaques using ASTM D412 Die C and tested at a pull rate of 50 mm per minute using an Instron Model 5969 tester. The tensile strength (MPa) was calculated as the peak force (Newtons) multiplied by the cross-sectional area (mm 2 ) and elongation was determined at the specimen break point, all in accordance with ASTM D412. Tensile strength and elongation results for adhesive samples were reported from an average of three specimens.
[0129] The tensile strength is preferably greater than 4 MPa, more preferably greater than 5 MPa, particularly preferably greater than 6 MPa. The elongation is preferably greater than 15% at break, more preferably greater than 25% at break, particularly preferably greater than 30% at break.
[0130] Impact peel test Impact peel specimens were prepared using E-coated (ED6100C) steel coupons measuring 25.4 mm wide, 101.6 mm long, and 0.8 mm thick. The adhesive sample was dispensed from a spiral static mixer onto one end of the E-coated steel coupon, which was then overlapped with the same E-coated steel coupon to create a 30 mm adhesive overlap at the end of the specimen and a bond line thickness of 1.2 mm. Impact peel specimens were cured at 23°C and 50% relative humidity for 7 days or as specified. The cured impact specimens were pre-bent into a V-shape at the other unbonded end and then tested with a normal impact mass of 23.7 kg at a speed of 2.4 m / s. The reported impact strength (Newtons / mm) is the average of the area between 45% and 90% of the displacement to failure, all in accordance with ISO 11343 [2003 04 01]. Typically, at least three specimens were tested and averaged for the adhesive sample.
[0131] The impact peel strength is greater than 8 N / mm, preferably greater than 10 N / mm, more preferably greater than 12 N / mm, and most preferably greater than 15 N / mm. The impact peel failure is preferably greater than 85% CF, more preferably greater than 95% CF, and most preferably 100% CF.
[0132] Thermal Conductivity The thermal conductivity of the two-part adhesive samples was measured using a Linseis Thermal Interface Material (TIM) tester. The adhesive samples were dispensed through a static mixer between two sheets of release paper and then pressed to form a circular plaque approximately 1 mm thick. The circular plaques were cured for 7 days at 23°C and 50% relative humidity (RH). The cured circular plaques were then cut into five separate specimens measuring 1 inch square and the thickness was measured again with a vernier caliper (approximately 1 mm). The thermal impedance of the adhesive samples was measured at five different thicknesses by stacking the specimens one by one at 25°C with a 30°C gradient across the samples and a pressure set at 0.3 MPa. Liquid silicone was used on both sides of each specimen to ensure good thermal contact between the specimen and the plate. The thermal conductivity (W / mK) of the adhesive samples was obtained from the thermal impedance plots, all according to ASTM D5470.
[0133] Electrical resistivity Two copper strips (50 mm long, 12 mm wide) were placed parallel, 50 mm apart, on a non-conductive surface such as cardboard. An adhesive bead (approximately 4 mm in diameter) was dispensed perpendicular to the two copper strips through a static mixer and passed through the center of the strips. The bead was cured for 7 days (or the specified time) at 23° C. and 50% relative humidity. The resistivity of the bead was determined using an electrical multimeter by contacting its two probes to the two copper strips.
[0134] The electrical resistivity is greater than 300,000 ohms, preferably greater than 500,000 ohms, and more preferably greater than 1×10 6 ohms, most preferably 2×10 6 It is super ohms.
[0135] Preparation of Comparative and Inventive Adhesives Table 2 shows the raw materials of Component A in Comparative Example 1 and Examples 1 to 4 of the present invention.
[0136] [Table 3]
[0137] Ingredients 1, 1a and 2 were placed in a container and mixed for 3 minutes at 1000 rpm using a FlackTek speed mixer, model DAC600.2 VAC-LR. Ingredient 3 was then added and mixing continued for another 3 minutes at 1000 rpm. The temperature of the mixture was raised to 54°C and mixing continued for another 2 minutes at 1000 rpm. Ingredients 4, 5 and half of 6 were added and mixing continued for 2.5 minutes. Ingredient 7 and the remaining half of ingredients 4, 5 and 6 were added and mixing continued for 2.5 minutes at 1000 rpm. Finally, the entire mixture was mixed under vacuum at 1000 rpm for 3 minutes. The finished material was packaged in airtight tubes.
[0138] Table 3 shows the raw materials of Component B in Comparative Example 1 and Examples 1 to 4 of the present invention.
[0139] [Table 4]
[0140] Ingredients 1, 1a-d (1d was preheated at 54°C for 2 hours before use), 2 and 3 were placed in a container and mixed for 1 minute at 1000 rpm using a FlackTek speed mixer, model DAC600.2 VAC-LR (1d can also be added after ingredient 3 is already mixed). Half of ingredients 4, 5, 6 and 7 were added and mixing continued for 2.5 minutes at 1000 rpm. The remaining half of ingredients 4, 5, 6 and 7 were added and mixing continued for 2.5 minutes at 1000 rpm. Finally, the entire mixture was mixed under vacuum at 1000 rpm for 3 minutes. The finished material was packed into airtight tubes.
[0141] Tables 4 and 5 show the press flow viscosities of components A and B of comparative and inventive examples 2 and 4. Table 6 shows the Brookfield viscosities of components A and B of inventive examples 2 and 4.
[0142] [Table 5]
[0143] [Table 6]
[0144] [Table 7]
[0145] The adhesives were prepared by dispensing component A and component B in a 1:1 volume ratio using a spiral static mixer. The temperature of the components can be room temperature or a higher temperature such as 40° C. Curing was typically carried out for 7 days at 23° C. and 50% relative humidity (RH). The properties of the cured adhesives are shown in Tables 7, 8 and 9.
[0146] The adhesives all exhibited excellent thermal conductivity, greater than 1 W / mK. Lap shear strength was comparable for all adhesives, and all exhibited a failure mode of 100% cohesive failure. However, the inventive examples all exhibited significantly improved lap shear elongation at maximum stress compared to the comparative examples. Inventive sample 2 also exhibited a much better tensile elongation than the comparative samples. Inventive sample 4 exhibited a tensile elongation of 2×10 6 Both inventive samples 2 and 4 exhibited impact peel strengths of 18.4 N / mm and 21.1 N / mm, respectively.
[0147] [Table 8]
[0148] [Table 9]
[0149] [Table 10]
Claims
1. A thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising component A, (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B wherein at least one of the polyether polyols in Components A and B is poly(tetramethylene oxide) glycol, and the equivalent ratio of isocyanate from Component A to hydroxyl from Component B is from 0.8 to 2.
0.
2. The following limitations (i)-: (i) the at least one polyether polyol in Component B comprises poly(tetramethylene oxide) glycol; (ii) the at least one polyisocyanate (a1) comprises a polycarbodiimide-modified MDI; (iii) the at least one polyether polyol in component (B) comprises at least 8 weight percent poly(tetramethylene oxide) glycol, based on the total weight of component B; (iv) the equivalent ratio of the isocyanate from Component A to the hydroxyl from Component B is 0.9 to 1.5; (v) component A comprises poly(tetramethylene oxide) glycol; (vi) the at least one polyisocyanate (a1) comprises a difunctional isocyanate compound; 10. The thermally conductive two-part polyurethane adhesive composition of claim 1, further comprising one or more of:
3. 10. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein component A comprises a silane adhesion promoter.
4. 10. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein component A comprises an aminosilane adhesion promoter.
5. 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein the silane adhesion promoter is 3-trimethoxysilyl-N-(3-trimethoxysilylpropyl)propan-1-amine.
6. 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein said component B comprises a polyether polyol selected from diols, triols, and mixtures thereof.
7. Component B is a poly(propylene oxide) diol, poly(propylene oxide) triol, and Poly(tetramethylene oxide) diol 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, comprising:
8. Component B is poly(propylene oxide) diol having an average equivalent weight of 900 to 1,100 g / eq; poly(propylene oxide) diol having an average equivalent weight of 190 to 230 g / eq; a poly(propylene oxide) triol having an average equivalent weight of 70 to 100 g / eq; and Poly(tetramethylene oxide) diol 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, comprising:
9. Component B is, based on the total weight of component B, 8 to 14 weight percent of poly(propylene oxide) diol; 1.5 to 5 weight percent poly(propylene oxide) triol, and 5 to 15 weight percent poly(tetramethylene oxide) diol 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, comprising:
10. Component B is, based on the total weight of component B, 1 to 4 weight percent of a poly(propylene oxide) diol having an average equivalent weight of 900 to 1,100 g / eq; 7 to 14 wt. % of a poly(propylene oxide) diol having an average equivalent weight of 190 to 230 g / eq; 1.5 to 3 weight percent of a poly(propylene oxide) triol having an average equivalent weight of 70 to 100 g / eq, and 5 to 15 weight percent poly(tetramethylene oxide) diol 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, comprising:
11. 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein component B comprises 1,4-butanediol and component A comprises a polymeric MDI that contains MDI.
12. 2. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein the thermally conductive fillers (a2, b2) are selected from fillers having a thermal conductivity of greater than 5 W / m°K, greater than 10 W / m°K or greater than 15 W / m°K.
13. 10. The thermally conductive two-part polyurethane adhesive composition of claim 1, wherein the thermally conductive filler is present in the adhesive at a concentration of 65 to 85 weight percent, based on the total weight of the adhesive.
14. 10. The thermally conductive two-part polyurethane adhesive composition of claim 1 having a thermal conductivity of at or about 1.1 W / mK or greater after curing for 7 days at 23°C.
15. 1. A method for bonding two or more substrates, comprising the steps of: (1) providing a thermally conductive two-component polyurethane adhesive composition, the thermally conductive two-component polyurethane adhesive composition comprising: (A) a polyisocyanate component, component A, (a1) at least one polyisocyanate, (a2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component A; (a3) optionally a polyether polyol; (a4) optionally, a silane adhesion promoter A polyisocyanate component comprising component A, (B) a polyol component, component B, (b1) at least one polyether polyol; (b2) 40 to 85% by weight of a thermally conductive filler, based on the total weight of component B; (b3) a catalyst capable of catalyzing the reaction of an isocyanate with a polyol; (b4) optionally, a silane adhesion promoter A polyol component comprising component B at least one of the polyether polyols in component A and component B is poly(tetramethylene oxide) glycol, and the equivalent ratio of isocyanate from component A to hydroxyl from component B is from 0.8 to 2.0; (2) mixing component A and component B in a desired ratio to form the adhesive; (3) applying the adhesive to at least one substrate; (4) contacting a second substrate with the adhesive; and (5) A step of curing the adhesive The method includes:
Citation Information
Patent Citations
A two-component polyurethane adhesive made using an isocyanate-terminated quasi-prepolymer based on poly(butylene oxide)
JP2018524429A
Two-fluid curable urethane composition, adhesive including the same, and adhesion method using the same
JP2020152750A
Two-component polyurethane adhesive composition
JP2021519364A
Primerless polyurethane adhesive composition
JP2021528524A
Polypropylene bonding adhesive and method
JP2021529226A